Kinetics analysis of the thermal decomposition of poly(butylene adipate) ionomers by thermogravimetry (TG) and derivate (DTG) analysis - Yakuphanoğlu, Fahrettin; Yoo, Y. T. (Taylor & Francis Inc, 2006)
Kinetics analysis and thermal decomposition study of poly( butylene adipate) ionomers (PBAi) synthesized using the dimethyl 5-sulfoisophthalate sodium salt ( DMSI) of the diacid monomer were carried out by thermogravimetry (TG) and derivate (DTG) analysis. The decomposition kinetic parameters ( activation energy, frequency factor) were calculated. The activation energy values of the PBAi-2, PBAi-3 and PBAi-5 ionomers were respectively found as 164.51, 141.91 and 78.07 kJ/mol. The influence of DMSI content on the decomposition of the ionomers was investigated. The activation energy values decrease with increasing the content of DMSI. This suggests that increasing the content of DMSI makes the thermal decomposition of the ionomers easier.
Keywords: thermal analysis; ionomer; kinetic parameters